Urinary kallidinogenase for the treatment of cerebral arterial stenosis - Zhao L; Zhao Y; Wan Q; Zhang H (Dove Medical Press, 2015)
Liandong Zhao,1,2 Ying Zhao,2 Qi Wan,1 Haijun Zhang3 1Department of Neurology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, 2Department of Neurology, The Second People’s Hospital of Huai’an and The Affiliated Huai’an Hospital of Xuzhou Medical College, Huai’an, Jiangsu, 3Department of Oncology, Zhongda Hospital, Medical School, Southeast University, Nanjing, People’s Republic of China Aim: Urinary kallidinogenase (UK) has shown promise in improving cerebral perfusion. This study aimed to examine how UK affects cognitive status and serum levels of amyloid betas (Aβs) 1-40 and 1-42 in patients with cerebral arterial stenosis.Methods: Ninety patients with cerebral arterial stenosis were enrolled, of whom 45 patients received UK + conventional treatment (UK group), and 45 patients received conventional treatment alone as control group. Cognitive status and Aβ1-40 and Aβ1-42 serum levels were determined before treatment and at 4 weeks and 8 weeks after treatment.Results: At 4 weeks after treatment, cognitive status in patients treated with UK clearly improved accompanied by Aβ1-40 serum levels decreasing while there was no change of Aβ1-42. Cognitive status in patients receiving UK continued to improve, Aβ1-40 serum levels declined further as well as Aβ1-42 serum levels began to decrease dramatically at 8 weeks after treatment.Conclusion: UK could improve cognitive status and decrease both Aβ1-40 and Aβ1-42 serum levels to prevent ischemic cerebral injury, which represents a good option for patients with cerebral arterial stenosis.Keywords: urinary kallidinogenase, arterial stenosis, Alzheimer’s disease, Aβ1-40, Aβ1-42